2018
DOI: 10.3390/ijms19113432
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Natural Compound Falcarindiol Disrupts Neural Stem Cell Homeostasis by Suppressing Notch Pathway

Abstract: Neural stem cells (NSCs) are undifferentiated, multi-potent cells that can give rise to functional neurons and glial cells. The disruption in NSC homeostasis and/or the impaired neurogenesis lead to diverse neurological diseases, including depression, dementia, and neurodegenerative disorders. Falcarindiol (FAD) is a polyacetylene found in many plants, and FAD shows the cytotoxicity against breast cancers and colon cancers. However, there is no research on the consequence of FAD treatment in normal stem cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…To determine the anticancer activity of finasteride, we tested the effect of finasteride on glioblastoma stem-like cells, which has not been demonstrated so far. Previously, we showed that cancer stem-like cell populations were enriched by maintaining cells with serum-free culture media supplemented with epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) [ 14 ]. Under this sphere-forming condition, we treated two different glioblastoma cells, U373 and T98G, with finasteride and temozolomide.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the anticancer activity of finasteride, we tested the effect of finasteride on glioblastoma stem-like cells, which has not been demonstrated so far. Previously, we showed that cancer stem-like cell populations were enriched by maintaining cells with serum-free culture media supplemented with epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) [ 14 ]. Under this sphere-forming condition, we treated two different glioblastoma cells, U373 and T98G, with finasteride and temozolomide.…”
Section: Resultsmentioning
confidence: 99%
“…. Falcarinol and falcarindiol have also shown in other studies that they can lead to cell cycle arrest and apoptosis of cancer cells, which may be linked to their alkylating properties as described in the introduction [94,[142][143][144]. For example, it has been demonstrated that falcarindiol is able to induce ER stress in breast cancer cells (MDA-MB-231, MDA-MB-468 and SKBR3) leading to caspase-dependent cell death (apoptosis).…”
Section: Cytotoxic C 17 and C 18 Acetylenic Oxylipins From Other Planmentioning
confidence: 90%
“…In addition, falcarindiol contributed to autophagy-dependent cell death in these breast cancer cells and had synergistic effect with approved cancer drugs 5-fluorouracil and bortezomib in killing breast cancer cells [143]. Finally, it has been shown that falcarindiol may inhibit the growth of cancer stem cells by suppressing the Notch pathway, as demonstrated in neural stem cells [144]. The Notch pathway is vital to tumorigenicity of cancer stem cells, which are the driving force of tumor development [145].…”
Section: Cytotoxic C 17 and C 18 Acetylenic Oxylipins From Other Planmentioning
confidence: 99%
“…Interestingly, falcarindiol (3) has been shown to affect cell proliferation in a biphasic manner (hormesis) thus implying that benefits were achieved at non-toxic concentrations [38]. Recent pharmacological studies confirmed the anticancer activity of 3 against some selected cancer cells such as colonrectal cancer [39], breast cancer [40], and glioblastoma cells [41]. Based on the literature data, we decided to investigate the effects on the cell proliferation of new falcarindiol-derived compounds 4 and 5 compared with falcarindiol (3) and acetyl derivatives 1 and 2.…”
Section: Resultsmentioning
confidence: 99%